Finance and Inequality: Exploring Pro-Poor Investment Channels in Africa - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2011)
Hitherto very few studies on the inequality-finance(investment) nexus have focused on the African continent owing to lack of relevant data. This paper integrates previously missing investment and financial components in the assessment of how finance affects pro-poor investment channels. Findings reveal, but for the case of foreign investment, financial development dynamics of depth, efficiency, activity and size have an equalizing effect on income distribution through private, public and domestic investment channels. As a policy implication investment-targeted financial reforms that aim to curb poverty should take account of the disequalizing income-effect of foreign investment in undeveloped countries.
Keywords: D60; E25; G20; I30; O55; 330; Finance; Investment; Poverty; Inequality; Africa